Hyodeoxycholic acid inhibits colorectal cancer proliferation through the FXR/EREG/EGFR axis - Pang, Qiang; Huang, Shansong; Li, Xiaodong; Cao, Jiaqing (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe high morbidity and mortality rates of colorectal cancer (CRC) have been a public health concern globally, and the search for additional therapeutic options is imminent. Hyodeoxycholic acid (HDCA) has been receiving attention in recent years and has demonstrated potent efficacy in several diseases. Nonetheless, the antitumor effects and molecular pathways of HDCA in CRC remain largely unexplored.MethodsIn this study, we investigated how HDCA influences the growth potential of CRC cells using techniques such as flow cytometry, Edu assay, CCK-8, colony formation assay, Western blot analysis, and animal experiments.ResultsIt was found that HDCA treatment of CRC cells was able to significantly inhibit the proliferative capacity of the cells. Furthermore, it was discovered that HDCA primarily stimulated Farnesoid X Receptor (FXR) rather than Takeda G protein coupled receptor 5 (TGR5) to suppress CRC growth. It was also confirmed that HDCA inhibited the Epiregulin (EREG)/Epidermal Growth Factor Receptor (EGFR) pathway by activating FXR, and a negative correlation between FXR and EREG was analyzed in CRC tissue samples. Finally, in vivo animal studies confirmed that HDCA inhibited CRC proliferation without hepatotoxicity.ConclusionOur findings indicate that HDCA suppresses the EREG/EGFR signaling route by activating FXR, thereby hindering the growth of CRC cells and demonstrating a tumor-inhibiting effect in CRC. This study may provide a new therapeutic strategy to improve the prognosis of CRC.